Zero-hysteresis superelastic Co33Cr16Ti1Ga7Si7 alloy was designed through element doping: First-principle calculation - Wenbin Zhao; Yi Zhao; Haosen Yuan; Baoyin Liu; Renwei Chen; Jian Li; Changlong Tan (Journal of Materials Research and Technology)
Owing to the unique re-entrant martensitic transformation behavior, Co2Cr(Ga,Si) alloy received extensive attention and investigation. Nevertheless, the Co2Cr(Ga,Si) alloy exhibits pronounced stress hysteresis across a broad near-room temperature range, which limits their application in aerospace actuators. Significantly, this work calculated the stress-strain curve by doping four elements (Ti, Fe, Nb, Zr) via the first-principle calculation. It was found that the Ti-doped alloy has zero-stress hysteresis and low driving force. Moreover, the mechanism of zero-hysteresis and low driving force is revealed from the perspective of energy and electron respectively. From the energy perspective, the average rate of energy change explains that the zero-hysteresis of the Co33Cr16Ti1Ga7Si7 alloy is due to the lower energy dissipation during the phase transformation than the undoped alloy. The small change rate of Helmholtz free energy indicates that the Co33Cr16Ti1Ga7Si7 alloy has a low driving stress. From the electronic point of view, the density of states results demonstrate that the low driving force originate from the binding of d-orbitals among Ti, Co, and Cr elements, leading to a reduction in system energy and consequently requiring lower stress to induce the phase transformation. The charge density calculation results show that the interaction between Ti atoms and Co atoms in the Ti-doped alloy is weakened, leading to a decrease in driving force. Our research successfully designed the Co33Cr16Ti1Ga7Si7 superelastic shape memory alloy with zero-hysteresis and sheds light on the mechanism of superelasticity in shape memory alloy.